2013
DOI: 10.1590/s1517-83822013005000062
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian propolis protects Saccharomyces cerevisiae cells against oxidative stress

Abstract: Propolis is a natural product widely used for humans. Due to its complex composition, a number of applications (antimicrobial, antiinflammatory, anesthetic, cytostatic and antioxidant) have been attributed to this substance. Using Saccharomyces cerevisiae as a eukaryotic model we investigated the mechanisms underlying the antioxidant effect of propolis from Guarapari against oxidative stress. Submitting a wild type (BY4741) and antioxidant deficient strains (ctt1Δ, sod1Δ, gsh1Δ, gtt1Δ and gtt2Δ) either to 15 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 43 publications
(77 reference statements)
2
12
0
Order By: Relevance
“…braziliensis in vitro [64]. All of the extracts herein confirmed the antioxidant effects of propolis, as evidenced by significant decreases in nitric oxide and superoxide production [6569]. In addition, our results showed increased superoxide dismutase (SOD) activity following treatment by alcoholic and glycolic extracts.…”
Section: Discussionsupporting
confidence: 75%
“…braziliensis in vitro [64]. All of the extracts herein confirmed the antioxidant effects of propolis, as evidenced by significant decreases in nitric oxide and superoxide production [6569]. In addition, our results showed increased superoxide dismutase (SOD) activity following treatment by alcoholic and glycolic extracts.…”
Section: Discussionsupporting
confidence: 75%
“…fumigatus wild type, Δ rtfA , complementation, and OE rtfA strains to various concentrations of menadione. Menadione produces ROS once it enters the cell, creating an environment that is under oxidative stress [73]. Our results conclusively showed that rtfA is important for the response of A .…”
Section: Discussionsupporting
confidence: 68%
“…Many studies have shown, that phenolic compounds demonstrate the capacity to inhibition of lipid peroxidation in cells (Meng et al, 2017). This effect was also observed in yeast cells exposed to cadmium and blueberry extracts (Opera et al, 2014), yeast, and its mutant strains devoid of antioxidant enzymes and treated with cadmium and resveratrol (Dani et al, 2008), as well as yeast treated with propolis and quercetin in exposure to H 2 O 2 (de Sa et al, 2013).…”
Section: The Effect Of Onion Skin Extract On the Total Content Of Gmentioning
confidence: 87%
“…Cells were counted using Thoma counting chamber. The experiment was performed in triplicate (Dani et al, 2008;Tongul & Tarhan, 2016;Żyracka, 2014).…”
Section: Cell Growth Measurementmentioning
confidence: 99%